Extraction and characterization methods for titanium dioxide nanoparticles from commercialized sunscreens. Issue 1 (12th December 2017) - Philippe, Allan; Košík, Juraj; Welle, Alexander; Guigner, Jean-Michel; Clemens, Oliver; Schaumann, Gabriele E.
Abstract : Sunscreens are an important source of TiO2 nanoparticles in surface waters. Abstract : Sunscreens are an important source of TiO2 nanoparticles in surface waters. The fate and toxicity of these particles have not been fully addressed due to the gap between model nanoparticles usually used in studies and the more complex particles found in commercial products. Therefore, mild extraction methods for TiO2 nanoparticles from sunscreens were evaluated for providing more realistic nanoparticle samples for future studies. We propose two methods based on ultrafiltration and ultracentrifugation, respectively, for extracting TiO2 nanoparticles from sunscreens using a surfactant solution as the solvent. These methods were tested on eleven commercial sunscreens with differing compositions. The ultracentrifugation variant allows extracting 250 mg from approximately 5 g of sunscreen in one day. Recoveries for ultrafiltration and ultracentrifugation were 52–96% and 78–98%, respectively. Purification efficiency was determined for the ultracentrifugation variant by determining the avobenzone concentration in sunscreen extracts using UV-spectrometry and was high for all tested sunscreens. Transmission electron microscopy and dynamic light scattering revealed a high diversity in particle shape, although size parameters were comparable (average hydrodynamic diameter: 19–34 nm). Isoelectric points were below 4.6 for all sunscreen extracts. Time-of-flight secondary ion mass spectrometry revealed that probably all TiO2 particles were coated; most of them with PDMS, some others with Al- and Si-based materials. Comparison of images of particles inside the sunscreens using cryogenic transmission electron microscopy and of extracted particles showed that while the shape of the primary nanoparticles was not affected by the extraction, they were agglomerated inside the sunscreens. These agglomerates could be completely disrupted using ultrasonication. Therefore, the particles extracted in the present study can be considered as more environmentally relevant in terms of size, shape, surface charge and coating than model TiO2 nanoparticles.